LITERATURE STUDY ON THE ANTIBIOTIC RESISTANCE OF SALMONELLA SPP. IN THE HOUSEFLY AS A DISEASE VECTOR - Wea, Pasionista Karmeliana Bha; Kallau, Novalino Harold Geoffrey (Buletin Veteriner Udayana, 2025)
Vector-borne diseases transmitted by insects such as the housefly (Musca domestica) pose a serious threat to public health due to their potential to spread harmful pathogens and antibiotic-resistant bacteria. This study aims to determine the prevalence of Salmonella spp. in houseflies and their antibiotic resistance profiles through a literature review. The research was conducted using a descriptive qualitative method by reviewing national and international scientific journals published between 2003 and 2024. Collected data included the number of flies examined, sampling locations, number positive for Salmonella spp., types of antibiotics tested, and levels of resistance. The results showed that the prevalence of Salmonella spp. in houseflies ranged from 13.3% to 100%, with the highest rates found in areas with poor sanitation, such as traditional markets and landfills. Furthermore, the highest levels of antibiotic resistance were observed against erythromycin (97%), streptomycin (100%), tetracycline (90%), and amoxicillin (88–92.9%). In contrast, lower resistance levels were recorded for gentamicin (0–34.5%) and ciprofloxacin (6.25–33.3%). Based on these findings, it can be concluded that Musca domestica plays an important role as a vector in the transmission of antibiotic-resistant Salmonella spp. Therefore, similar studies are necessary to provide a foundation for understanding the spread of antimicrobial resistance and its impact on public health.